Preparation method of composite solid electrolyte membrane and solid-state battery

By optimizing the ratio of polymer matrix to inorganic ceramic fillers, and introducing crosslinking agents, and using ultraviolet crosslinking curing technology to prepare composite solid electrolyte membranes, it solves the safety hazards and insufficient performance problems of traditional lithium battery electrolytes, and achieves high ion The electrolyte membrane with conductivity and mechanical toughness improves the performance and safety of solid-state batteries.

CN119481238AInactive Publication Date: 2025-02-18ZHONGKE RONNENG (YANCHENG) TECH CO LTD

Patent Information

Application Number
CN202411612033.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The liquid electrolytes of traditional lithium batteries have safety hazards such as flammability and explosiveness, leakage risks, and the low ionic conductivity, poor interface contact, and insufficient mechanical toughness of solid electrolytes limit their commercialization process.

Method used

By selecting polymer matrix and inorganic ceramic filler and adding crosslinking agents and photoinitiators, the composite solid electrolyte membrane is prepared by ultraviolet crosslinking curing technology to optimize the ionic conductivity and mechanical toughness of the membrane.

Benefits of technology

The high ionic conductivity of the electrolyte membrane is achieved, the fast charging and discharging requirements of solid-state batteries is met, the safety and cycle life of the battery are improved, and the material has good chemical and thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481238A_ABST
    Figure CN119481238A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite solid electrolyte membrane. The preparation method specifically comprises the following steps: S1, selecting and proportioning raw materials; s2, preparing a solution; s3, coating and curing; s4, carrying out post-treatment; s5, assembling the battery; s6, performance testing; the invention relates to the technical field of new energy materials. According to the preparation method of the composite solid-state electrolyte membrane and the solid-state battery, by optimizing the ratio of the polymer matrix to the inorganic ceramic filler and introducing the cross-linking agent to enhance an ionic conduction path, high ionic conductivity of the electrolyte membrane is achieved, and the requirement for rapid charging and discharging of the solid-state battery is met; the formation of the cross-linked structure significantly improves the mechanical toughness of the electrolyte membrane, effectively prevents the deformation and fracture of the battery in the charging and discharging process, improves the safety and the cycle life of the battery, and the selected material has good chemical stability and thermal stability, and is suitable for industrial production. And stable operation of the electrolyte membrane in a wide temperature range and in a complex electrochemical environment is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to a method for preparing a composite solid electrolyte membrane and a solid-state battery. Background Art

[0002] With the rapid development of electric vehicles and large-scale energy storage equipment, higher requirements are placed on battery safety and energy density. Traditional lithium batteries use organic liquid electrolytes, which have safety hazards such as low boiling point, low flash point, flammability and volatility, which greatly restrict the development of high-energy lithium secondary batteries. Therefore, all-solid-state batteries that use solid electrolytes to replace traditional organic liquid electrolytes are expected to fundamentally solve the battery safety problem and are ideal chemical power sources for electric vehicles and large-scale energy storage equipment. However, the electrolyte membrane in solid-state batteries is in solid form and has deficiencies in lithium ion conductivity. In order to enable the battery to obtain good charge and discharge performance, the ionic conductivity of the solid electrolyte membrane has become the focus of improvement.

[0003] With the rapid development of electric vehicles, energy storage systems and portable electronic devices, higher requirements are placed on the energy density, cycle life and safety of lithium-ion batteries. Traditional liquid electrolytes are inflammable, explosive, and have leakage risks, which limit the application of lithium-ion batteries in certain high-risk fields. Solid-state electrolytes are regarded as one of the key technologies for the next generation of lithium-ion batteries due to their non-flammable, leakage-free, and compatibility with high-energy-density positive electrode materials. However, solid-state electrolytes face challenges such as low ionic conductivity, poor interface contact, and insufficient mechanical toughness, which limit their commercialization process. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing a composite solid electrolyte membrane and a solid-state battery, which solve the problems mentioned in the above background technology.

[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a composite solid electrolyte membrane, specifically comprising the following steps:

[0006] S1. Raw material selection and proportion: select polymer matrix, inorganic ceramic filler, add a certain amount of cross-linking agent, and at the same time, add a small amount of photoinitiator to promote the cross-linking reaction;

[0007] S2. Solution preparation: dissolve the above raw materials in anhydrous acetonitrile to form a uniform and transparent solution, add an appropriate amount of surfactant, the mass of the solvent accounts for 30% of the total mass;

[0008] S3, coating and curing: Use the scraper method or spin coating method to evenly coat the solution on the polytetrafluoroethylene substrate, and then irradiate under ultraviolet light for cross-linking and curing. The ultraviolet light intensity is 800-1200mW / cm2 , the irradiation time is 1-10 minutes, after which the film is placed in a vacuum oven at 60-100°C for 24-48 hours to remove residual solvent;

[0009] S4, post-processing: peeling the dried film from the substrate, performing necessary cutting and packaging to obtain the final composite solid electrolyte membrane. In order to improve the ionic conductivity of the membrane, the membrane can also be subjected to ion exchange treatment;

[0010] S5. Battery assembly: Assemble the positive electrode, the negative electrode and the composite solid electrolyte membrane prepared above into a sandwich structure, and use appropriate packaging technology to ensure the sealing of the internal environment of the battery;

[0011] S6. Performance testing: Conduct electrochemical performance tests on the assembled solid-state batteries, including charge and discharge cycle stability, rate performance, self-discharge performance, and safety performance tests, to verify their feasibility in practical applications.

[0012] Preferably, in S1, the mass ratio of each raw material is 100:(20-35):(10-25):(0.5-3), and the photoinitiator is any one or more of benzoin and its derivatives, benzil derivatives, dialkoxyacetophenone, α-hydroxyalkyl phenone, α-aminoalkyl phenone, acylphosphine oxide, benzophenone and its derivatives, thioxanthone, anthraquinone, diaryliodonium salt, triarylsulfonium salt and arylferrocenium salt.

[0013] Preferably, the cross-linking agent containing carbon-carbon double bonds is one or more of 1,6-hexanediol diacrylate, ethoxylated trimethylolpropane triacrylate, and polyurethane acrylate.

[0014] Preferably, the polymer matrix is ​​any one or more of polyvinylidene fluoride-hexafluoropropylene, polyvinyl alcohol, polyacrylonitrile, and polyvinylidene fluoride, and the inorganic ceramic filler is any one or more of LAGP, LATP, LLTO, LLZTO, LLZO, AlO, SiO, and TiO.

[0015] Preferably, the mass ratio of the polymer matrix, the inorganic ceramic filler, the cross-linking agent containing carbon-carbon double bonds and the organic solvent is 1:(0.08-0.14):(0.4-0.8):(3.5-6.5), and the surfactant is sodium dodecyl sulfate.

[0016] Preferably, in S5, in order to improve the cycle stability and safety of the battery, a buffer layer may be provided between the positive electrode and the electrolyte membrane, and between the negative electrode and the electrolyte membrane.

[0017] The present invention also discloses a solid-state battery using the composite solid electrolyte membrane prepared by the method, comprising a positive electrode, a negative electrode and the composite solid electrolyte membrane between the positive electrode and the negative electrode.

[0018] Beneficial Effects

[0019] The present invention provides a method for preparing a composite solid electrolyte membrane and a solid-state battery. Compared with the prior art, the present invention has the following beneficial effects: the method for preparing the composite solid electrolyte membrane and the solid-state battery specifically include the following steps: S1, raw material selection and proportioning; S2, solution preparation; S3, film coating and curing; S4, post-processing; S5, battery assembly; S6, performance testing; by optimizing the proportion of the polymer matrix and the inorganic ceramic filler, and introducing a cross-linking agent to enhance the ion conduction path, the high ion conductivity of the electrolyte membrane is achieved, and the demand for fast charging and discharging of the solid-state battery is met. The formation of the cross-linked structure significantly improves the mechanical toughness of the electrolyte membrane, effectively prevents the deformation and rupture of the battery during the charging and discharging process, and improves the safety and cycle life of the battery. The selected materials have good chemical stability and thermal stability, which ensures the stable operation of the electrolyte membrane in a wide temperature range and in a complex electrochemical environment. The entire preparation process uses non-toxic and environmentally friendly raw materials and solvents, which is in line with the development trend of green chemistry. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a flow chart of the steps of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] See also Figure 1 The present invention provides a technical solution: a method for preparing a composite solid electrolyte membrane, which specifically includes the following embodiments:

[0023] Embodiment 1

[0024] S1. Raw material selection and proportion: select a polymer matrix and an inorganic ceramic filler, add a certain amount of a crosslinking agent, and at the same time, add a small amount of a photoinitiator to promote the crosslinking reaction, and mix them in a mass ratio of 1:0.1:0.01:0.5:5 to obtain a mixed solution;

[0025] S2. Solution preparation: dissolve the above raw materials in anhydrous acetonitrile to form a uniform and transparent solution, add an appropriate amount of surfactant, the mass of the solvent accounts for 30% of the total mass;

[0026] S3, coating and curing: Use the scraper method or spin coating method to evenly coat the solution on the polytetrafluoroethylene substrate, and then irradiate under ultraviolet light for cross-linking and curing. The ultraviolet light intensity is 1000mW / cm 2 , the irradiation time was 5 min, after which the film was dried in a vacuum oven at 80 °C for 36 h to remove the residual solvent;

[0027] S4, post-processing: peeling the dried film from the substrate, performing necessary cutting and packaging to obtain the final composite solid electrolyte membrane. In order to improve the ionic conductivity of the membrane, the membrane can also be subjected to ion exchange treatment;

[0028] S5. Battery assembly: Assemble the positive electrode, the negative electrode and the composite solid electrolyte membrane prepared above into a sandwich structure, and use appropriate packaging technology to ensure the sealing of the internal environment of the battery;

[0029] S6. Performance testing: Conduct electrochemical performance tests on the assembled solid-state batteries, including charge and discharge cycle stability, rate performance, self-discharge performance, and safety performance tests, to verify their feasibility in practical applications.

[0030] Embodiment 2

[0031] S1. Raw material selection and proportion: select a polymer matrix and an inorganic ceramic filler, add a certain amount of a crosslinking agent, and at the same time, add a small amount of a photoinitiator to promote the crosslinking reaction, and mix them in a mass ratio of 1:0.12:0.015:0.6:4.5 to obtain a mixed solution;

[0032] S2. Solution preparation: dissolve the above raw materials in anhydrous acetonitrile to form a uniform and transparent solution, add an appropriate amount of surfactant, the mass of the solvent accounts for 30% of the total mass;

[0033] S3, coating and curing: Use the scraper method or spin coating method to evenly coat the solution on the polytetrafluoroethylene substrate, and then irradiate under ultraviolet light for cross-linking and curing. The ultraviolet light intensity is 800mW / cm 2 , the irradiation time was 1 min, after which the film was dried in a vacuum oven at 60 °C for 24 h to remove the residual solvent;

[0034] S4, post-processing: peeling the dried film from the substrate, performing necessary cutting and packaging to obtain the final composite solid electrolyte membrane. In order to improve the ionic conductivity of the membrane, the membrane can also be subjected to ion exchange treatment;

[0035] S5. Battery assembly: Assemble the positive electrode, the negative electrode and the composite solid electrolyte membrane prepared above into a sandwich structure, and use appropriate packaging technology to ensure the sealing of the internal environment of the battery;

[0036] S6. Performance testing: Conduct electrochemical performance tests on the assembled solid-state batteries, including charge and discharge cycle stability, rate performance, self-discharge performance, and safety performance tests, to verify their feasibility in practical applications.

[0037] Embodiment 3

[0038] S1. Raw material selection and proportion: select a polymer matrix and an inorganic ceramic filler, add a certain amount of a crosslinking agent, and at the same time, add a small amount of a photoinitiator to promote the crosslinking reaction, and mix them in a mass ratio of 1:0.1:0.01:0.7:4 to obtain a mixed solution;

[0039] S2. Solution preparation: dissolve the above raw materials in anhydrous acetonitrile to form a uniform and transparent solution, add an appropriate amount of surfactant, the mass of the solvent accounts for 30% of the total mass;

[0040] S3, coating and curing: the solution is evenly coated on the polytetrafluoroethylene substrate by a doctor blade method or a spin coating method, and then irradiated under ultraviolet light for cross-linking and curing. The ultraviolet light intensity is 1200mW / cm2 and the irradiation time is 10 minutes. After that, the film is placed in a vacuum oven at 100°C for 48 hours to remove residual solvent;

[0041] S4, post-processing: peeling the dried film from the substrate, performing necessary cutting and packaging to obtain the final composite solid electrolyte membrane. In order to improve the ionic conductivity of the membrane, the membrane can also be subjected to ion exchange treatment;

[0042] S5. Battery assembly: Assemble the positive electrode, the negative electrode and the composite solid electrolyte membrane prepared above into a sandwich structure, and use appropriate packaging technology to ensure the sealing of the internal environment of the battery;

[0043] S6. Performance testing: Conduct electrochemical performance tests on the assembled solid-state batteries, including charge and discharge cycle stability, rate performance, self-discharge performance, and safety performance tests, to verify their feasibility in practical applications.

[0044] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0045] Effect Example

[0046] The ionic conductivity and elastic modulus of the composite electrolyte membranes prepared in the above-mentioned Examples 1 to 3 and the electrolyte membranes of the comparative example are shown in the following table.

[0047]

[0048] In summary: by optimizing the ratio of polymer matrix and inorganic ceramic filler, and introducing cross-linking agent to enhance the ion conduction path, the high ion conductivity of the electrolyte membrane is achieved to meet the needs of fast charging and discharging of solid-state batteries. The formation of cross-linked structure significantly improves the mechanical toughness of the electrolyte membrane, effectively prevents deformation and rupture of the battery during charging and discharging, and improves the safety and cycle life of the battery. The selected materials have good chemical stability and thermal stability, which ensures the stable operation of the electrolyte membrane in a wide temperature range and complex electrochemical environment. The entire preparation process uses non-toxic and environmentally friendly raw materials and solvents, which is in line with the development trend of green chemistry.

[0049] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0050] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a composite solid electrolyte membrane, characterized in that: The specific steps include: S1. Raw material selection and proportion: select polymer matrix, inorganic ceramic filler, add a certain amount of cross-linking agent, and at the same time, add a small amount of photoinitiator to promote the cross-linking reaction; S2. Solution preparation: dissolve the above raw materials in anhydrous acetonitrile to form a uniform and transparent solution, add an appropriate amount of surfactant, the mass of the solvent accounts for 30% of the total mass; S3, coating and curing: Use the scraper method or spin coating method to evenly coat the solution on the polytetrafluoroethylene substrate, and then irradiate under ultraviolet light for cross-linking and curing. The ultraviolet light intensity is 800-1200mW / cm 2 , the irradiation time is 1-10 minutes, after which the film is placed in a vacuum oven at 60-100°C for 24-48 hours to remove residual solvent; S4, post-processing: peeling the dried film from the substrate, performing necessary cutting and packaging to obtain the final composite solid electrolyte membrane. In order to improve the ionic conductivity of the membrane, the membrane can also be subjected to ion exchange treatment; S5. Battery assembly: Assemble the positive electrode, the negative electrode and the composite solid electrolyte membrane prepared above into a sandwich structure, and use appropriate packaging technology to ensure the sealing of the internal environment of the battery; S6. Performance testing: Conduct electrochemical performance tests on the assembled solid-state batteries, including charge and discharge cycle stability, rate performance, self-discharge performance, and safety performance tests, to verify their feasibility in practical applications.

2. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: In S1, the mass ratio of each raw material is 100:(20-35):(10-25):(0.5-3), and the photoinitiator is any one or more of benzoin and its derivatives, benzil derivatives, dialkoxyacetophenone, α-hydroxyalkyl phenone, α-aminoalkyl phenone, acylphosphine oxide, benzophenone and its derivatives, thioxanthone, anthraquinone, diaryliodonium salt, triarylsulfonium salt and arylferrocenium salt.

3. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The cross-linking agent containing carbon-carbon double bonds is one or more of 1,6-hexanediol diacrylate, ethoxylated trimethylolpropane triacrylate, and polyurethane acrylate.

4. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The polymer matrix is ​​any one or more of polyvinylidene fluoride-hexafluoropropylene, polyvinyl alcohol, polyacrylonitrile, and polyvinylidene fluoride, and the inorganic ceramic filler is any one or more of LAGP, LATP, LLTO, LLZTO, LLZO, AlO, SiO, and TiO.

5. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The mass ratio of the polymer matrix, the inorganic ceramic filler, the cross-linking agent containing carbon-carbon double bonds and the organic solvent is 1:(0.08-0.14):(0.4-0.8):(3.5-6.5), and the surfactant is sodium dodecyl sulfate.

6. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: In the above S5, in order to improve the cycle stability and safety of the battery, a buffer layer may be provided between the positive electrode and the electrolyte membrane, and between the negative electrode and the electrolyte membrane.

7. A solid-state battery using a composite solid electrolyte membrane prepared by the method according to any one of claims 1 to 6, characterized in that: It comprises a positive electrode, a negative electrode and the composite solid electrolyte membrane between the positive electrode and the negative electrode.

Citation Information

Patent Citations

  • Rapid photocuring electrolyte composition and preparation method and application thereof

    CN116154271A

  • Composite solid-state electrolyte membrane for solid-state battery and preparation method of composite solid-state electrolyte membrane

    CN117219876A

  • Composite solid electrolyte film, preparation method thereof and solid-state battery

    CN118136941A

  • Composition of Nanoparticle Based on Organic-inorganicHybrid and Nanocomposite Polymer Electrolyte forLithium Polymer Rechargeable Batteries

    KR1020070013840A

  • Organic-inorganic complex solid polymer electrolytes membrane, manufacturing method thereof and all solid battery including thereof

    KR1020160079405A

Cited By

  • Inorganic-organic composite solid electrolyte, membrane material thereof, preparation method and solid-state battery

    CN120709490A